Carpet boom and its factors in the South Caucasus of Tsarist Russia - Hasan Abdi; Jafar Aghazadeh (تاریخ اسلام و ایران)
Gravestone motifs, travelogues, works by Western painters and the identification of valuable carpets in museums, private galleries, and historical exhibitions indicate the prosperity of carpet weaving in the South Caucasus. The geographical and cultural conditions as well as state support provided suitable conditions for the flourishing of carpet weaving in the South Caucasus. Women were more active in this field than men, and it was rare for a family not to own a carpet loom. The quality and favourable price of carpets from this region also ensured a high demand in Europe, further contributing to prosperity. This paper is structured using a descriptive-analytical approach and a qualitative method based on content analysis and examines the question of which factors played a decisive role in the prosperity of carpet weaving in the region. The research hypothesis is based on the idea that the prosperity of carpet weaving in the South Caucasus was a function of natural factors, government policies, and high demand. The findings of this research show that carpet weaving flourished more in the South-Eastern Caucasus than in other areas and that concern for income had a greater impact on the significant prosperity of carpet weaving than natural factors and government support.